The coming Russian boom a guide to new markets and politics - Layard, Peter R. G. 1934-; Parker, John 1954- (Free Press, 1996)
Since the fall of the soviet empire in 1991, Westerners have been speculating about the future of its vast and long-oppressive economy. Politicians, economists, and businesspeople alike have watched with great interest as the new Russia has scrambled to get on its feet. As support for the communists has waned and waxed, Westerners have worried: Are Russia's troubles merely the growth pains of a rich new market waiting to take off? Or should businessmen and tourists stay away? The bottom line, argue Richard Layard and John Parker, is a healthy and strong one. Democracy and free markets have taken root in Russia for good. The authors offer a soup-to-nuts analysis of the Russian economy, along with its political and social underpinnings, to demonstrate just how successful the reforms have been and what they mean for Western businessmen.
Keywords: Politieke situatie; Sociaal-economische situatie; Politik; Politische Situation; Wirtschaft; Prognose; Russie - Politique et gouvernement - 1991-2000; Russia (Federation) -- Politics and government -- 1991-; Russland